Caracterização ultraestrutural de terminações nervosas autonômicas e expressão de neurotrofinas (NGF E BDNF) e seus receptores no coração de modelo experimental da doença de Chagas - Natália Katley Oliveira (2017)
The present study evaluated ultrastructural alterations of autonomic varicosities and the expression of the neurotrophins NGF (Nerve Growth Factor) and BDNF (Brain Derived Neurotrophic Factor) in addition to their receptors, TrkA, TrkB and p75, in the ventricles of rats experimentally infected with Y strain of Trypanosoma cruzi. Ventricular samples of animals with 13, 20, 30 and 60 days of infection (di) and of their controls were prepared for transmission electron microscopy analysis. Immunofluorescence was used to verify the density of nerve fibers and the expression of receptors in the myocardium. Quantification of levels of NGF and BDNF was achieved by ELISA. It was observed severe denervation of the myocardium at 13 and 20 di, and both cholinergic and adrenergic varicosities presented important ultrastructural signs of degeneration, like reduction in number and alteration in the morphology of vesicles of neurotransmitters. At 30 and 60 di there was partial reinnervation of the myocardium and both degenerate and normal varicosities could be observed. Cardiac NGF levels rose significantly at 20 di, while NGF serum levels were higher at 13 di. Cardiac BDNF levels did not change in infected animals, but were reduced in the blood at 13 and 20 di. At 13 di, TrKA receptor expression was elevated, especially in vascular endothelial areas of the myocardium. At 20 di the immunoreactivity was also greater but diffuse throughout the myocardium. The TrkB receptor expression was higher at 30 di and diffuse in the myocardium, while that of p75 increased at 20 di, but was restricted to interstitial areas. These data suggest a participation of NGF and BDNF, via their both high and low affinity receptors, in the degenerative and regenerative phenomena of cardiac autonomic nerve fibers that occur along the chagasic infection. The actions of neurotrophins appear to occur with different kinetics and involve different elements present in the myocardium. The participation of other neurotrophins and pro-neurotrophins is considered.